Reach Out! Highlighting Collections and Expanding Outreach to Non-Traditional Communities across Academia. Issue 1 (2nd January 2019) - Beene, Stephanie; Jackson, Amy S.; Kostelecky, Sarah; Quinn, Todd
ABSTRACT: As the number of reference questions continues to decline across academic libraries, innovative models have been developed to highlight collections and reach underserved communities. This article describes four outreach models at the University of New Mexico University Libraries, including satellite outreach services, pop-up book trucks and events, and relationship building at various locations on and off campus. The authors describe innovative approaches including curated browsing experiences and relationship marketing to underserved communities. Lessons learned, future approaches, and the benefits of each model will also be explored.